Adaptive Leadership and New Normal Work Environment on the Performance of National Police Health Center Employees in the Covid 19 Pandemic Era - Efri Susanto; Prista Tarigan; Yoga Fortuna Wisnu Wardana (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The National Police Medical and Health Center (Pusdokkes) is the supervisor of the Police Medical and Health function at the National Police Headquarters level which is the spearhead in realizing health insurance for National Police/ASN personnel and their families as well as the general public. The performance of employees in government-owned public service organizations, in fact, cannot be measured materially or financially, but can be seen in the completion of the existing volume or workload, quality of service and timeliness by using resources to achieve organizational goals that are in line with the field of work carried out. by employees. The research aims to determine the influence of Adaptive Leadership and the New Normal Work Environment on the Performance of National Police Health Center Employees in the Covid 19 Pandemic Era. This research uses Quantitative. The results of this research show that Adaptive Leadership and the New Normal Work Environment have an influence on the Performance of National Police Health Center Employees in the Covid 19 Pandemic Era.